Methods for the investigation of work and human errors in rail engineering contexts - Farooqi, Aaisha Tasneem (2016)
It is important to study accidents and their underlying causes, in order to generate recommendations for improving system safety. A range of methods have been developed in various industries, to understand how accidents have occurred, as well as identify potential human errors in systems.